Changes in the level of relationship between invertebrates and society of pre-service primary school teachers, after an educational intervention - Esteve, P.; Jaén, M.; Banos-González, I. (Journal of Biological Education, 2021)
This study explores the progression in the perceptions that pre-service primary teachers have about the interdependence of people and invertebrate organisms, after implementing an inquiry proposal. By means of an inductive analysis, the reports made by the pre-service teachers were assessed and grouped into four models, according to the level of relationship between invertebrates and society they established. The results suggest that the participants had certain willingness to build simple relationships. Nevertheless, the progression towards more-complex relationships based on an understanding of the ecosystem services provided by invertebrates would require opportunities for the pre-service teachers to explore their direct and indirect relationships with their everyday life. Moreover, the utilitarian vision of invertebrates as a resource might not be enough to understand the complexity of conservation problems, which requires a systemic vision to interpret the causes and consequences in the different environmental, socio-economic dimensions.
Keywords: Training teachers; educational intervention; invertebrates; knowledge